The Process of Supervision of Human Resources in Improving Work Discipline for Civil Servants (Study at the Berkas Village Office, Teluk Segara District, Bengkulu City) - Fitriansyah Fitriansyah; Yusuarsono Yusuarsono; Antonio Imanda (Penerbit Jurnal Indonesia, 2021)
This study intends to determine the process of supervising human resources in improving the work discipline of civil servants. (Study at the Berkas Kelurahan Office, Teluk Segara Subdistrict, Bengkulu City. The purpose of this study is to identify and describe the Supervision of Human Resources in Improving the Work Discipline of Civil Servants. This study uses a qualitative descriptive research method. The technique used is Accident Cluster Sampling, a collection technique The data in this study are observation, interviews, and documentation.The theory of the stages in supervision according to Kadarman (2001:161), among others, can be concluded: Determination of Implementation Standards (Planning) for the Head of the Village Office in carrying out supervision and work discipline has been implemented and implemented based on the regulations of the Law of the Republic of Indonesia number 5 of 2014 concerning the State Civil Apparatus of Government Employees with a Work Agreement, hereinafter abbreviated as PPPK, Determination of Measurement of the Implementation of Leadership Activities in this case Mrs. n all employees from planning to implementation of activities, Comparing the Implementation of Activities with Standards and Analyzing Deviations In the implementation of activities there are problems, especially getting information from superiors suddenly so that there is no preparation at all, the room has a very limited capacity and cannot accommodate more people large, and the condition of covid 19 so that activities are reduced or even eliminated and the Correctional Action taken by the leadership at the File Head Office has never changed the rules regarding employee discipline in entering work. Because these rules are standard and obeyed by all ASN in Indonesia and must be implemented by all employees.